Strategi Komunikasi Satgas Penaganan Covid 19: Analisis pada Akun Facebook BPBD Kabupaten Blitar - Rohmatul hidayah Rohmatul hidayah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
Mass media plays an important role in dealing with the Covid-19 pandemic, especially in the online media Facebook. The importance of communication provides effectiveness in conveying information. Through clear and clear communication, the information conveyed will be received easily even in difficult situations. The purpose of writing this article is to provide an explanation and description of the communication strategy carried out by the Blitar Regency BPBD Covid-19 Handling Task Force through a Facebook account. This research was conducted using descriptive qualitative. The results of the research in this paper explain that through social media Facebook the information obtained makes it easier for people from various circles. In addition, with social media on Facebook, the community can play an active role in providing opinions, ideas, and input in handling Covid-19